Relationship between number of brushings per day and DMFT in 12-year-old schoolchildren, in the City of Cuenca - Ecuador 2016 - Ibarra Quezada, Jehidy Cristina (2022)
Objective: To determine the relationship between the number of brushings per day and DMFT in 12-year-old schoolchildren from the Gil Ramírez Dávalos Parish, Cuenca-Ecuador 2016. Materials and methods: The study was quantitative approach, descriptive design, documentary scope and retrospective temporality. The files that contained the information were obtained from the database that rests in the research department of the Catholic University of Cuenca, in the Epi Info system of the Dentistry career, which correspond to the macro study of the "Epidemiological Map of Oral Health ”Of the City of Cuenca, which is made up of the information of 188 records of 12-year-old schoolchildren belonging to the Gil Ramírez Dávalos parish, of the City of Cuenca - Ecuador, 2016. Results: From the data obtained, the most High corresponds to the frequency of brushing three times a day in 65.4% women, and in men a percentage of 52.5% represents the frequency of brushing less than three times a day. Furthermore, it was established that the DMFT index for both sexes is "medium". Conclusion: There is no association between the number of brushings per day and the DMFT index, as there is no relationship between the two variables according to sex.